Reflexões críticas sobre aspectos produtivos e do trabalho na biblioteca universitária em tempos de crise: comparação entre Brasil, Espanha e Moçambique - André de Souza Pena (2015)
The Academy has always been challenged to have an answer to its contemporary social cravings. This thesis is based on a comparative approach between Brazil, Spain and Mozambique and draws on interviews and secondary information sources to calculate in those regions the role of academic libraries in face of the international crisis, which began in 2008. These countries are going through a critical political and economic moment – each one with its particularities. Spain has shown high unemployment rate as a consequence of the crisis. Brazil, even in face of one of the worst crisis in the capitalism, has found a way to get around it, despite its huge and evident social inequality, which intensely calls for the need of a plan on a great expansion and popularization of the university education, as a possibility to minimize, in a long term, this scene. Mozambique has been struggling for a virtuous insertion in the international economy, as it tries to expand its industry, and, as doing so, contributes to the university education and scientific production growth and, even with high levels of poverty, provides a way to face the crisis. This thesis has analyzed and compared governmental policies based on the work process in academic libraries – one in each country – trying to raise the following aspects: the political and social role of the public university as a way out of the crisis, the role of the academic library in this specific situation and, finally, the existence of economic stimulation for national and/or regional initiatives concerning policies on the librarian labor market, reading incentive programs, adopted material support for information and its free access. Even though there is still an ideological menace around the librarian‘s profession, it was possible to observe some stability of its labor market during the crisis, mainly in Brazil, compared to the other two analyzed countries in this thesis. This work has also verified the essential function of the book and the library in the cultural transmission, as the maintenance of paper as the main informational material support in the academic library. It could also be verified that electronic devices produce more waste, which are a risk to the environment and toxic to humans, being also more obsolete compared to books. Among other issues, attention was also paid to the existence of conflict of interest to what concerns free access, as well as to the power of paid periodicals, which come from AngloSaxon countries. Finally, this work looks forward to the recovery of a human approach, in which the work reassumes its value of use, and hopes librarians to be technical, an artisan and critical, in order to aid in the social transformation through culture and help to overcome the crisis to come from the new spirit of capitalism.